NEW MYLODONTOIDEA (XENARTHRA, PHYLLOPHAGA) FROM THE MIDDLE MIOCENE-PLIOCENE OF VENEZUELA - Carlini A.A.; Scillato-Yane G.J.; Sanchez R. (My University, 2006)
Two new genera of Mylodontoidea, Mirandabradys and Bolivartherium, and five new species, M. socorrensis (Socorro Formation, Middle Miocene), M. urumaquensis and B. urumaquensis (Urumaco Formation, Upper Miocene), M. zabasi and B. codorensis (Codore Formation, Pliocene) are described. There is a high diversity of tardigrades from Middle Miocene to Pleistocene sites of Northern Venezuela. Almost all the recorded species are large and close to the size of the late Pleistocene Glossotherium robustum or Lestodon armatus. This implies that either the 'faunas' were composed only of large-sized tardigrades, or that the smaller taxa are missing because of taphonomic bias and that the faunal diversity was actually higher than currently indicated.
Keywords: MIRANDABRADYS; BOLIVARTHERIUM; NEW TAXA; TERTIARY; GROUND SLOTHS; SOUTH AMERICA; Pleistocene; Pliocene; Miocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен